Collaborative Housing Research (1990–2017): A Systematic Review and Thematic Analysis of the Field. Issue 1 (1st January 2020) - Lang, Richard; Carriou, Claire; Czischke, Darinka
ABSTRACT: Europe is witnessing a new wave of collective self-organized forms of housing provision. We refer to the wide variety of these forms under the umbrella term "Collaborative Housing". Alongside growing grassroots activity, the number and breadth of academic publications is rapidly growing. Nevertheless, the field remains thematically fragmented, with literature spread across disciplines. This article aims to establish a basis for greater conceptual clarity by exploring the domain of collaborative housing research over the period of 1990–2017. We carry out a thematic mapping and assessment covering 195 relevant peer-reviewed journal articles in English, German and French. These are inductively synthesized and categorized into five main thematic areas: socio-demographic, collaboration, motivation, effects and context. We conclude that the systematic and inductive approach of our review unravels new perspectives and makes the case for the conceptualization of collaborative housing as an independent research field, providing a basis for further theory development.